Generalized Kuhn-Tucker conditions for N-firm stochastic irreversible investment under limited resources - Maria B. Chiarolla; Giorgio Ferrari; Frank Riedel (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
In this paper we study a continuous time, optimal stochastic investment problem under limited resources in a market with N firms. The investment processes are subject to a time-dependent stochastic constraint. Rather than using a dynamic programming approach, we exploit the concavity of the profit functional to derive some necessary and sufficient first order conditions for the corresponding Social Planner optimal policy. Our conditions are a stochastic infinite-dimensional generalization of the Kuhn-Tucker Theorem. As a subproduct we obtain an enlightening interpretation of the first order conditions for a single firm in Bank [SIAM Journal on Control and Optimization 44 (2005)]. In the infinite-horizon case, with operating profit functions of Cobb-Douglas type, our method allows the explicit calculation of the optimal policy in terms of the 'base capacity' process, i.e. the unique solution of the Bank and El Karoui representation problem [Annals of Probability 32 (2004)].
urn:nbn:de:0070-pub-26717275
Keywords: C02; E22; D92; G31; 330; stochastic irreversible investment; optimal stopping; the Bank and El Karoui Representation Theorem; base capacity; Lagrange multiplier optional measure; Investition; Sunk Costs; Stochastischer Prozess; Suchtheorie; Nichtlineare Optimierung; Theorie